The effects on children of depressed mothers' remission and relapse over 9 months. Issue 13 (October 2014) - Weissman, M. M.; Wickramaratne, P.; Pilowsky, D. J.; Poh, E.; Hernandez, M.; Batten, L. A.; Flament, M. F.; Stewart, J. W.; Blier, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The high rate of depression among children of depressed mothers is well known. Suggestions that improvement in maternal acute depression has a positive effect on the child have emerged. However, data on the mechanisms of change have been sparse. The aim was to understand how remission and relapse in the mother might explain the changes in the child's outcome. Method Participants were 76 depressed mothers who entered into a medication clinical trial for depression and 135 of their eligible offspring ages 7–17 years. The mothers and children were assessed at baseline and periodically over 9 months by independent teams to understand the relationship between changes in children's symptoms and functioning and maternal remission or relapse. The main outcome measures were, for mothers, the Hamilton Depression Rating Scale (HAMD), the Social Adjustment Scale (SAS) and the Parental Bonding Instrument (PBI) and, for children, the Children's Depression Inventory (CDI), the Columbia Impairment Scale (CIS), the Multidimensional Anxiety Scale for Children (MASC) and the Children's Global Assessment Scale (CGAS). Results Maternal remission was associated with a decrease in the child's depressive symptoms. The mother's subsequent relapse was associated with an increase in the child's symptoms over 9 months. The effect of maternal remission on the child's improvement was partially explained by an improvement in the mother's parenting, particularly the change in the mother's ability to listen and talk to her child, but also reflected in her improvement in parental bonding. These findings could not be explained by the child's treatment. Conclusions A depressed mother's remission is associated with her improvement in parenting and a decrease in her child's symptoms. Her relapse is associated with an increase in her child's symptoms.